Toby Wilkinson and Susan Sherratt, (eds) Circuits of Metal Value. Changing Roles of Metals in the Early Aegean and Nearby Lands. Sheffield Studies in Aegean Archaeology, 14. - Alvarez, Laura E. (Journal of Greek Archaeology, 2025)
In April 2016 a Round Table was held at the University of Sheffield, almost a decade after the seminal 1997 conference Metals Make the World Go Round, organised by Christopher Pare, which was a landmark survey of Bronze Age metallurgy, already highlighting the scope and importance of metals in influencing social and political dynamics. This new volume emerging from these discussions brings together seven of the twelve papers presented, coherently reunited around discussions concerning the movement of raw metal materials, the transmission of technical knowledge, and the evolving composition of metal alloys, overall presenting a fresh re-evaluation of archaeological research on metal technology. A key theme running through the contributions is the idea that the adoption of new methods is contingent upon the presence of interactive factors and a conducive social context, such as changing needs, or reconfigurations of the existing relationships within certain segments of the community. The result is a well-structured and accessible 214- page volume illustrated with monochrome images throughout, offering a stimulating reassessment of the role of metallurgy in shaping ancient economies and societies while engaging with broader debates on technological and cultural transmission in the wider Mediterranean as well as the Near East.